2011
DOI: 10.1111/j.1365-2966.2011.19016.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the polarization properties of Comet 1P/Halley using a mixture of compact and aggregate particles

Abstract: Both the in situ measurement of Comet 1P/Halley and the Stardust‐returned samples of Comet Wild 2 showed the presence of a mixture of compact and aggregate particles, with both silicates and organic refractory being in the composition of the cometary dust. Results obtained recently from the Stardust mission suggest that the overall ratio of compact to aggregate particles is 65:35 (or 13:7) for Comet 81P/Wild 2. In the present work, we propose a model that considers cometary dust as a mixture of compact and agg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Mie theory, the scattering of light by transparent spherical particles, qualitatively replicates many of the polarization features seen in cometary dust, but aspherical particles (either irregular polydisperse submicron particles or porous aggregates of submicron components) are needed to completely explain the polarization and other scattering properties (Kolokolova et al, 2004). Recent work suggests that cometary particles consist of a mixture of aggregates and compact solid particles (Kolokolova and Kimura, 2010;Das et al, 2011). Much work has been done using the T-matrix method (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mie theory, the scattering of light by transparent spherical particles, qualitatively replicates many of the polarization features seen in cometary dust, but aspherical particles (either irregular polydisperse submicron particles or porous aggregates of submicron components) are needed to completely explain the polarization and other scattering properties (Kolokolova et al, 2004). Recent work suggests that cometary particles consist of a mixture of aggregates and compact solid particles (Kolokolova and Kimura, 2010;Das et al, 2011). Much work has been done using the T-matrix method (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We utilize this concept to explore the NPB and its dependencies on various physical parameters. This negative polarization, on the other hand proves the availability of silicate materials in the dust particles [9,10,11,12]. It has been suggested that near field effect and the constructive interference of multiply scattered waves give rise to the phenomenon of negative polarization in dust particles though there is no direct evidence or reason behind the actual cause of negative polarization [13].…”
Section: Introductionmentioning
confidence: 99%
“…We also checked on some examples that both (4) and ( 5) gave very similar values of the polarization. However, under a different situation, the linear polarization should be expressed by (5).…”
Section: Computed Optical Parametersmentioning
confidence: 99%